They are more beautiful than me! How social media use increases women’s body-related envy and cosmetic surgery consideration - Li, Minhui; Li, Xingming; Yang, Feng; Zhang, Tianning (Frontiers in Psychology, 2025)
BackgroundPast research has indicated the close connection between social media use and women’s envy, but so far, no research has been conducted to exclusively examine the effect and mechanism of social media use on women’s body-related envy.ObjectiveTo fill this gap, with TikTok as a representative example of video-based social media, four studies (N = 767) were conducted to explore whether and how social media use increases women’s body-related envy, and the subsequent downstream consequences.Method and resultsIn Study 1a, we employed an online questionnaire survey and found that TikTok use had a significantly positive prediction on women’s body-related envy. In Study 1b, we temporarily activated the TikTok use state in the lab and found that participants in the TikTok use priming condition reported greater body-related envy than those in the control condition. In Study 2, we divided TikTok use into active and passive TikTok use and then applied an online questionnaire survey to examine the relationship and mechanism between active/passive TikTok use and women’s body-related envy. The results showed that passive TikTok use, rather than active TikTok use, had a significant prediction on women’s body-related envy, and appearance upward comparison played a fully mediating role between them. In Study 3, we conducted an online experiment to explore the downstream consequences related to women’s body-related envy. The results showed that, partially via the mediating role of body-related envy, passive TikTok use further increased women’s cosmetic surgery consideration.ConclusionPassive social media use can significantly increase women’s body-related envy via the mediating role of appearance upward comparison. And the increased body-related envy will further increase women’s cosmetic surgery. The present research contributes to understanding how social media use increases women’s body image concerns and appearance enhancement intentions.